Biomechanical comparison of reverse offset‐L osteotomy and chevron osteotomy in cadaveric hallux valgus surgery - Cingoz, Tunca; Ziroglu, Nezih; Bozdag, Ergun; Yamak, Fatih; Yozgatli, Tahir Koray; Bayramoglu, Alp; Kocaoglu, Baris; Esemenli, Behic Tanil (Wiley, 2024)
AbstractObjectiveChevron osteotomy offers near‐excellent clinical results and adequate stability at lower shift percentages, among the techniques used to correct hallux valgus deformity. This cadaveric study aimed to compare the Chevron osteotomy with the reverse offset‐L osteotomy, which may provide a greater surface area and a more stable geometry to withstand higher cantilever forces at higher shift percentages.MethodsMetatarsal bones obtained from 20 human cadavers with similar bone quality were divided into two groups: Chevron osteotomy was applied to the 1st group and reverse offset‐L osteotomy was applied to the 2nd group. The load‐to‐failure, displacement in the y‐axis, and total displacement values of both groups were compared statistically. Furthermore, bone densities were compared between the groups with computed tomography imaging.ResultsWhen outliers in both groups were excluded, a statistically significant difference was found in favor of reverse offset‐L (143 ± 42 vs. 204 ± 51.2 N, p = 0.02) in terms of failure load. The groups were similar in terms of displacement on the y‐axis and total displacement values. Bone densities were similar.ConclusionThe reverse offset‐L osteotomy has been shown to withstand greater loads before failure compared to the standard Chevron osteotomy. This significant difference in load‐to‐failure may enable reverse offset‐L to provide reliable stability in osteotomies performed in advanced HV cases requiring higher shifts.
Keywords: bunion; Male; metatarsal; Diseases of the musculoskeletal system; Middle Aged; Great toe; Bunion; biomechanics; Osteotomy; Biomechanical Phenomena; Metatarsal; RC925-935; Bone Density; Cadaver; Cadaver study; Humans; Biomechanics; cadaver study; Female; Hallux Valgus; great toe; Metatarsal Bones; Original Research; Aged